Comparison of intensive light-emitting diode and intensive compact fluorescent phototherapy in non-hemolytic jaundice - Takcı, Sahin; Yiğit, Sule; Bayram, Gülperi; Korkmaz, Ayşe; Yurdakök, Murat (The Turkish Journal of Pediatrics, 2013)
In severe and rapidly increasing jaundice, the use of intensive phototherapy provides greater effectiveness and a faster decrement in bilirubin levels compared to conventional phototherapy. The aim of this study was to compare the effectiveness of two types of intensive phototherapy: intensive compact fluorescent tube (CFT) and intensive light-emitting diode (LED) phototherapy. Forty-three infants over 35 weeks of gestation with severe non-hemolytic hyperbilirubinemia were enrolled in the prospective study. All infants received multidirectional (circular-shaped) intensive phototherapy. Of these, 20 infants received CFT while 23 infants received LED phototherapy. Bilirubin levels and body temperatures were measured periodically, and the rates of bilirubin decrement were calculated. Mean serum bilirubin level of the 43 infants was 20.5±1.5 mg/dl at the beginning of the therapy and mean duration of phototherapy was 20.6±1.1 hours. The rate of mean bilirubin decline was 47.2% and the decrease was more prominent in the first four hours (0.84 ± 0.41 mg/dl/h). The rates of bilirubin decrement were comparable between the LED and CFT groups. Slightly elevated mean body temperature (37.1ºC) was determined in the CFT group (p